Comparative Analysis of Selected Metadata Standards for the Processing of Intangible Cultural Heritage - Anida Ibričić (Bosniaca)
Goal: Intangible cultural heritage represents “living” culture transmitted from previous to future generations, making it vital to preserve the cultural identity of a people. In this regard, and considering that no comparative analysis of metadata standards for the processing of intangible cultural heritage in the digital environment has been carried out, this work aims to offer metadata standards that will apply to the processing of this type of heritage. Methodology: The research was performed by analyzing Dublin Core, CCO, VRA Core, CDWA, and MODS metadata standards. Along with the assessment of their quality using a descriptive method, and their comparative analysis, the applicability of selected metadata standards for the processing of intangible cultural heritage was examined on the example of the Jumps from the Old Bridge in Mostar, which represent the intangible cultural heritage of Bosnia and Herzegovina. Results: The research results through the research questions of the work show that of the selected metadata standards, Dublin Core and MODS can be used for the processing of intangible cultural heritage, which illustrates an example of metadata processing with metadata chosen standards. Discussion: The application of Dublin Core and MODS metadata standards for the processing of intangible cultural heritage is confirmed by examples of good practice in cultural institutions in Europe and the world. Both metadata standards, through the description of the digital object described by a set of descriptive elements, enable better organization and management of the digital object online. Besides being used to describe various objects and being widely acceptable, the advantages of these standards compared to other standards are that they contain elements that offer a detailed description of an object of intangible cultural heritage expressed in XML syntax. Also, the simplicity of implementation and high interoperability of both standards facilitate meta-search over the global network and access to the necessary information in the digital environment. Originality: This research represents the first research of its kind that provides a comparative analysis of selected metadata standards for the processing of intangible cultural heritage. The importance of the existence of metadata standards is reflected in the key role in the contribution to the preservation of cultural heritage, which especially refers to the intangible cultural heritage of Bosnia and Herzegovina for future generations and the promotion of its importance in a wider social and cultural context.